Disorders of Kidney Function in Chronic Heart Failure - Kamilova Umida; Abdullaeva Charos; Atakhodjaeva Gulchehra; Beknazarova Saida; Masharipova Dilyafruz; Ikramova Feruza (Institute of Medico-legal Publications Pvt Ltd, 2021)
The formation of cardiorenal syndrome (CRS) in patients with chronic heart failure (CHF) is a naturalmanifestation of a functionally interrelated process at the organ level. Moreover, impaired renal function is acommon and independent factor in the progression of the disease, a high incidence of cardiovascular eventsand death in a population of patients with asymptomatic and / or clinically manifested CHF, which is dueto the pathogenetic features of the formation of cattle in patients with CHF of ischemic genesis. The articleprovides an overview of studies on the pathogenesis of kidney damage in CHF, the role of various markersin the early diagnosis of cattle. A decrease in glomerular filtration rate (GFR) and an increase in urinaryalbumin excretion are currently considered as “renal” markers of a poor prognosis within the cardiorenalcontinuum. In this regard, for stratification of patients by stages of chronic kidney disease (CKD) and,consequently, for assessing the risks of increased overall and cardiovascular mortality in patients with CHF,the accuracy of calculating GFR, as the main indicator reflecting the severity of formed kidney damage, is ofgreat importance. Microalbuminuria is one of the early signs of CKD, the main cause of which is glomerularcapillary endothelial dysfunction that occurs in most patients with CHF. The presence and persistence ofsubclinical renal dysfunction during treatment, even with the achievement of risk factors (RF) control andregression of organ lesions, can adversely affect the patient’s prognosis. Assessment of the functional stateof the kidneys is important for early diagnosis, selection of effective preventive measures and treatment. Thetherapeutic strategy in patients with CHF in combination with CKD should be based on the nephroprotectiveeffects of drugs.